2020
DOI: 10.1002/ece3.6024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in prey color patterns for background matching across a continuous heterogeneous environment

Abstract: In heterogeneous habitats, camouflage via background matching can be challenging because visual characteristics can vary dramatically across small spatial scales. Additionally, temporal variation in signaling functions of coloration can affect crypsis, especially when animals use coloration seasonally for intraspecific signaling (e.g., mate selection). We currently have a poor understanding of how wild prey optimize background matching within continuously heterogeneous habitats, and whether this is affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Our study is the first to consider the effect on the performance of specialist and generalist targets of having more than two background types available. This more closely mimics natural situations, given that animals might not only travel between multiple distinct patches for various purposes, but may also have to contend with naturally heterogeneous backgrounds, varying both in space and time (Endler 1978 , 1984 ; Baling et al 2020 ). In Experiment 2, where targets were encountered on four different background types, we found a similar time-varying effect of strategy on survival to the two-background scenario in Experiment 1, where, on average, the population of specialists initially suffers a greater detection risk in the first few seconds of search, but later outperform generalists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is the first to consider the effect on the performance of specialist and generalist targets of having more than two background types available. This more closely mimics natural situations, given that animals might not only travel between multiple distinct patches for various purposes, but may also have to contend with naturally heterogeneous backgrounds, varying both in space and time (Endler 1978 , 1984 ; Baling et al 2020 ). In Experiment 2, where targets were encountered on four different background types, we found a similar time-varying effect of strategy on survival to the two-background scenario in Experiment 1, where, on average, the population of specialists initially suffers a greater detection risk in the first few seconds of search, but later outperform generalists.…”
Section: Discussionmentioning
confidence: 99%
“…New methods for quantifying camouflage and the similarity between prey animals and their natural habitats, from the perspective of potential predators, have shown that many species are locally adapted to specific backgrounds ( Harris and Weatherall 1991 ; Boratyński et al 2014 ; Marshall et al 2015 ; Niu et al 2017 ; Yamamoto and Sota 2020 ), and that these small improvements in background matching can have beneficial effects on survival ( Troscianko et al 2016 ). Yet, despite the difficulty of conclusively demonstrating that natural color patterns operate as generalists ( Cuthill 2019 ), putative generalist morphs are thought to exist in several species, including shrimp ( Duarte et al 2016 ), crabs ( Nokelainen et al 2019 ), and skinks ( Baling et al 2020 ), and there is evidence that imperfect camouflage can provide some protection from observers (Nokelainen et al 2019 , 2020 ; Rodríguez-Gironés and Maldonado 2020 ; Barnett et al 2021 ). In turn, empirical tests using artificial setups of the effectiveness of generalist and specialist strategies in nonhuman animals broadly support the predictions of theoretical models, suggesting that compromise patterns can be successful, and that their relative benefits depend on background similarity ( Merilaita et al 2001 ; Bond and Kamil 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…They report that the colour patterns of the pale-speckled moth is an effective cryptic match to the crustose lichen Lecanora conizaeoides, in both human-vision and ultra-violate visions to the crustose lichens. However, the camouflage behaviour in animals via matching habitat does not essentially depend on lichens (Walton & Stevens 2018), because habitat types and their background characteristics can largely vary across time and space and other factors like vegetation might play a role in camouflage as well (Baling et al 2019). For example, the melanic form of the peppered moth is adapted closely to plain tree barks, whereas the speckled form adapted to the crustose lichens (Walton & Stevens 2018).…”
Section: Lichens and Animal Camouflage In Central Asian Mountain Ecor...mentioning
confidence: 99%
“…One of the fitness-relevant traits that support survival and foster evolutionary adaptation is camouflage (Pèrez i de Lanuza & Font 2016; Cuthill 2019; Price et al 2019;Smith & Ruxton 2020). Camouflage is a trait or mechanism by which animals match or tune their body pattern to the background of their habitat, often varying over time and space and across populations (Baling et al 2019;Cuthill 2019;Smith & Ruxton 2020). Animals employ camouflage in multiple ways to facilitate various strategies including; background matching (i.e., animals resemble the shape of the habitat background) and disruptive coloration (i.e., developing high contrast patches to break up the body's edge).…”
mentioning
confidence: 99%
“…The extent of heterogeneity in natural environments, where animals experience continuous variation in both the number and proportion of different microhabitat types, as well as in their visual similarity [ 39 ], cannot be fully captured by experiments with a simple dichotomous set-up, in which prey occur on one of only two distinct patch types. A more sophisticated method, testing targets continuously varying in several properties, suggests that optimal camouflage can be achieved by adopting the most probable features of the scene, for both colour and pattern [ 40 ].…”
Section: Introductionmentioning
confidence: 99%